2003
DOI: 10.1074/jbc.m213214200
|View full text |Cite
|
Sign up to set email alerts
|

Suprachiasmatic Nucleus Circadian Oscillatory Protein, a Novel Binding Partner of K-Ras in the Membrane Rafts, Negatively Regulates MAPK Pathway

Abstract: Suprachiasmatic nucleus circadian oscillatory protein (SCOP) is a member of the leucine-rich repeat (LRR)-containing protein family. In addition to circadian expression in the rat hypothalamic suprachiasmatic nucleus, SCOP is constitutively expressed in neurons throughout the rat brain. Here we found that a substantial amount of SCOP was localized in the brain membrane rafts, in which only K-Ras was abundant among Ras isoforms. SCOP interacted directly through its LRR domain with a subset of K-Ras in the guani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 39 publications
(48 reference statements)
2
85
0
Order By: Relevance
“…PHLPP1 and PHPPL2 are considered to be tumor suppressors because they suppress cell survival, both by inhibiting proliferative pathways and by promoting apoptotic pathways (23). PHLPP in membrane rafts of rat brains can negatively regulate the proliferative RAS-mitogen-activated protein kinase (MAPK) pathway (39). Furthermore, human PHLPP1 and PHLPP2 can differentially regulate proliferative AKT signaling by selectively dephosphorylating the hydrophobic motifs of AKT2 or AKT3.…”
Section: Discussionmentioning
confidence: 99%
“…PHLPP1 and PHPPL2 are considered to be tumor suppressors because they suppress cell survival, both by inhibiting proliferative pathways and by promoting apoptotic pathways (23). PHLPP in membrane rafts of rat brains can negatively regulate the proliferative RAS-mitogen-activated protein kinase (MAPK) pathway (39). Furthermore, human PHLPP1 and PHLPP2 can differentially regulate proliferative AKT signaling by selectively dephosphorylating the hydrophobic motifs of AKT2 or AKT3.…”
Section: Discussionmentioning
confidence: 99%
“…20 In addition, both PHLPP1 and PHLPP2 have been shown to dephosphorylate PKCa and PKCbII, whereas PHLPP1 has also been implicated in the negative regulation of the Ras/Raf/MEK/ERK pathway. 22,23 Recently, several lines of evidence have suggested that PHLPP1 and PHLPP2 are involved in the pathogenesis of various types of cancer. Reduced or absent expression of PHLPP1 and PHLPP2 has been reported in approximately 80% of primary colorectal cancer specimen.…”
Section: Introductionmentioning
confidence: 99%
“…This arrangement allows for the existence of small, organized membrane microdomains called rafts (1)(2)(3)(4)(5) that orchestrate and regulate a number of signaling processes (6)(7)(8)(9)(10)(11)(12)(13). In order to elucidate mechanisms involved in these processes, it is crucial to understand raft biology.…”
mentioning
confidence: 99%